Generic roles: reducing code replication - Barbosa, Fernando Sérgio Rodrigues de Brito da Mota (2013)
In partial fulfillment of requirements for the degree of Doctor of Philosophy in Informatics Enginnering by the Doctoral Program in Informatics Engineering